Analisis Kadar Bilangan Peroksida Pada Minyak Kelapa Yang Ditambahkan Daun Sirsak (Annona muricata Linn) Dengan Metode Iodometri - manik, desima; Sungkawa, Hendra Budi; Indrawati, Ratih (poltekkes kemenkes pontianak, 2022)
Processing of coconut oil among the people is still mostly done traditionally by heating. The oil produced has poor quality and is easily rancid. This is because heating can change the oil structure. To overcome this, we need a way that can produce quality oil with a long shelf life. Therefore, there is a need for substances that can improve the quality of oil, named antioxidants. One of the natural antioxidants that can be utilized is soursop leaves. Antioxidants in soursop leaves are acetogenin, steroids, flavonoids, glycosides, interquinone and other active substances.This study aims to analyze the effect of adding soursop leaves to the value of peroxide in coconut oil with iodometry method. The method used in this study was quasi experimental with purposive sampling. The population in this study was coconut oil. The samples in this study are coconut oil without the addition of soursop leaves and coconut oil which was added to the soursop leaves with a concentration of 1.25%, 2.5% and 5%. Based on the results of the statistical analysis of linear regression, it was found that p value = 0.038 <a 0.05 so that there was an effect of adding soursop leaves to the value of peroxide in coconut oil with a contribution of 92.5%.Â